Public Budget and Economic Growth as Determinants of Unemployment Reduction in Post-Conflict and Post-Tsunami Aceh Province (Evidence from Aceh, 2005-2024) - Syahril Syahril (universitas teuku umar, 2026)
This study aims to examine the role of the Aceh Regional Budget (APBA) and economic growth in reducing unemployment in Aceh Province following the armed conflict and the tsunami disaster at the end of 2004. The observation period covers 2005–2024, which represents a crucial phase of reconstruction, rehabilitation, and long-term development in Aceh. This research adopts a quantitative approach using time series regression analysis. Secondary data are obtained from Statistics Indonesia (BPS), official APBA budget reports, and other relevant government publications. The empirical results show that the Aceh Regional Budget (APBA) has a negative and statistically significant effect on the unemployment rate, indicating that increased public spending contributes effectively to employment creation in Aceh. Conversely, economic growth exhibits a positive but statistically insignificant relationship with unemployment, suggesting the presence of jobless or less inclusive growth during the post-disaster and post-conflict period. This finding implies that economic expansion alone does not automatically translate into higher labor absorption. The study highlights the importance of improving the quality and allocation of public expenditure, particularly toward labor-intensive sectors. In conclusion, reducing unemployment in post-conflict regions such as Aceh requires sustained fiscal capacity and inclusive employment-oriented growth strategies. The results provide valuable policy insights for regional governments in designing future development policies for areas recovering from conflict and natural disasters.Keywords: Public budget, economic growth, unemployment